2022
DOI: 10.3389/fpls.2021.785653
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Physiological Responses of Three Psammophytes to Combined Effects of Warming and Precipitation Reduction in Horqin Sandy Land, Northeast China

Abstract: The decreasing precipitation with global climate warming is the main climatic condition in some sandy grassland ecosystems. The understanding of physiological responses of psammophytes in relation to warming and precipitation is a possible way to estimate the response of plant community stability to climate change. We selected Lespedeza davurica, Artemisia scoparia, and Cleistogenes squarrosa in sandy grassland to examine the effect of a combination of climate warming and decreasing precipitation on relative w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…However, at the maturation stage, the three enzyme activities were remarkably reduced by WT-CK compared to NT-CK. Previous research has found that, facing oxidative stress in plants from heat stress, variable responses in the form of an increase or reduction in the activities of antioxidant enzymes were found, but the results are usually incremental, which were consistent with our experimental results of enzyme activities from seeding to booting stages [27,43,44]. The different results were mainly related to the genotype, temperature, and duration [27,43,44].…”
Section: Antioxidant Enzyme Activities Of Leavessupporting
confidence: 91%
“…However, at the maturation stage, the three enzyme activities were remarkably reduced by WT-CK compared to NT-CK. Previous research has found that, facing oxidative stress in plants from heat stress, variable responses in the form of an increase or reduction in the activities of antioxidant enzymes were found, but the results are usually incremental, which were consistent with our experimental results of enzyme activities from seeding to booting stages [27,43,44]. The different results were mainly related to the genotype, temperature, and duration [27,43,44].…”
Section: Antioxidant Enzyme Activities Of Leavessupporting
confidence: 91%
“…The study area belongs to the typical temperate semiarid continental monsoon climate. The average annual precipitation was 351.7 mm ( Huang et al., 2022 ), with an uneven spatial and temporal distribution, in which the precipitation from June to September accounted for about 80%. The mean annual temperature is 5.8–6.4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The landscape in this area is characterized by sand dunes that alternate with gently undulating lowland areas ( Luo et al., 2020 ). This area belongs to the continental semiarid monsoon climate and is in the temperate zone, with a mean annual temperature of 3–7°C and a mean annual rainfall (AP) of 350–500 mm ( Huang et al., 2022 ). In recent years, many ecological problems have been caused by rapid population growth and increased demand for land, food, housing, and employment ( Kooch et al., 2022 ), especially the decline of the groundwater level ( Maihemuti et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The elevation in our study site is 327 m. This region belongs to a typical temperate continental monsoon climate, with an annual average temperature of 5.8–6.4°C and an average annual precipitation of 351.7 mm. The spatial and temporal distribution of rainfall is uneven, with approximately 80% of the precipitation occurring from June to September ( Huang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%